2022
DOI: 10.3390/molecules27041292
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Phytochemical Profiles and Antioxidant Potentials of Olive Leaves from 32 Cultivars Grown in China

Abstract: Olives (Olea europaea L.) are a significant part of the agroindustry in China. Olive leaves, the most abundant by-products of the olive and olive oil industry, contain bioactive compounds that are beneficial to human health. The purpose of this study was to evaluate the phytochemical profiles and antioxidant capacities of olive leaves from 32 cultivars grown in China. A total of 32 phytochemical compounds were identified using high-performance liquid chromatography–electrospray ionization–tandem mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
(67 reference statements)
4
19
0
Order By: Relevance
“…Furthermore, as reported by Lachowicz et al ( 44 ), the initial chemical compositions of different saskatoon berry cultivars potentially influenced the alterations of the polyphenolic compounds during convective drying. Therefore, these inconsistent results might also be correlated with the used cultivars, as the phytochemical compounds in the olive leaves differed among the different cultivars ( 45 ). Moreover, ultrasound-assisted extraction was employed to recover the phenolic compounds in this study, which potentially influenced phenolic extraction ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as reported by Lachowicz et al ( 44 ), the initial chemical compositions of different saskatoon berry cultivars potentially influenced the alterations of the polyphenolic compounds during convective drying. Therefore, these inconsistent results might also be correlated with the used cultivars, as the phytochemical compounds in the olive leaves differed among the different cultivars ( 45 ). Moreover, ultrasound-assisted extraction was employed to recover the phenolic compounds in this study, which potentially influenced phenolic extraction ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…It showed a UV absorption maximum at 345 nm for band I characteristic for flavones. The EIC at m/z 447.11 with its strong fragment at m/z 285, due to the loss of a hexose residue, indicates luteolin-O-hexoside (22). Luteolin-7-O-glucoside was previously detected as a major compound in olive leaf extracts as well as in the fruits 17 .…”
mentioning
confidence: 95%
“…Both the acetone-water and the hydroalcoholic extracts showed a content of luteolin-7-O-glucoside in the range of some Spanish, Croatians cultivars growing in Morocco, as well as for a Nocellara del Belice cv. growing in China [ 53 , 54 , 61 , 62 ] and in line with Benincasa et al [ 63 ], who investigated the leaf extract of the most common variety of Calabrian cultivars. Based on the higher level of phytochemical compounds in acetone-water leaf extract from Nocellara del Belice cv., a dry extract, rich in phenolic compounds, has been obtained, using a polystyrene resin.…”
Section: Discussionmentioning
confidence: 76%
“…the oleuropein level, in the leaves harvested in June, is comparable with the levels observed in our study, although the solvents used for the extraction were different [ 35 ]. In addition, the hydroalcoholic (50%, v / v ) extract from Nocellara contained oleuropein within the literature-reported range [ 53 , 54 ]. Unexpectedly, the lowest content of oleuropein was determined in Carolea cv., with the extract obtained using EtOH-water, although Nicolì et al [ 55 ], reported higher level of the secoiridoid in the same cultivar.…”
Section: Discussionmentioning
confidence: 76%